The inhibitory properties of acidic functionalised calix[4]arenes on human papillomavirus pentamer formation - Goh, Ching Yong; Fu, D.Y.; Duncan, Caitlin; Tinker, Adam; Li, F.; Mocerino, Mauro; Ogden, Mark; Wu, Y. (TAYLOR & FRANCIS LTD, 2020)
© 2020 Informa UK Limited, trading as Taylor & Francis Group.